Effects of Keemun and Dianhong Black Tea in Alleviating Excess Lipid Accumulation in the Liver of Obese Mice: A Comparative Study - Liao, Wenjing; Liu, Suyu; Chen, Yunxi; Kong, Yashuai; Wang, Dongxu; Wang, Yijun; Ling, Tiejun; Xie, Zhongwen; Khalilova, Irada; Huang, Jinbao (Frontiers in Nutrition, 2022)
The chemical compositions of black teas differ greatly and may have different health benefits; however, systematic investigations into such benefits are lacking. Here, the chemical profiles of Keemun black tea (KBT) and Dianhong black tea (DBT), two common categories of tea in China, were analyzed, and their lipid-lowering effects in mice were investigated. The compounds most crucial in differentiating KBT and DBT were determined to be phenolic compounds, theanine, and D-psicose. DBT was more effective than KBT in preventing excess hepatic fat accumulation. Both black teas effectively and comparably altered the mRNA levels of hepatic lipid–metabolizing genes. DBT had more favorable effects in stimulating fecal fat excretion than did KBT. The differentiating compounds with the higher values of variable importance in the projection (VIP) might predominantly contribute to the different health benefits; however, the most essential compound or combination of compounds requires clarification.